(3eONd eYGUQ aj GdeMGSHI GdeGdjI GdeJbOeIs - (3ceGd GdOjf eUWai(B, (3GdOgQGhjs ((3GdGScfOQjI(B:s (3GdecJH GdLGeYj GdMOjK(B,s, 2006)
(3GdeMGSHI Yf GfXeGe h GfOeGL GdTQcGJ hYf GdGSJKeGQGJ WhjdI GdCLd , JLejY GdbhGFe GdeGdjI aj JGQjN GdTQGA haj JGQjN dGMb dJGQjN GdTQGA hGYOGO GdbhGFe GdeLeYI eY hLhO GdYedjGJ GdeJHGOdI Hjf GdTQcI GdbGHVI h GdTQcI GdJGHYI hGdeMGSHI Yf GdeYGedGJ HGdYedI GdCLfHjI hJQLeI GdbhGFe GdeGdjI GdebGSI HGdYedI GdGLfHjI , GdJbGQjQ GdbWGYjI eY hLhO CSFdI h JeGQjf aj fgGjI cG aUd (B.s
Keywords: (3GdeGdjIs; (3GdeMGSHIs; (3eMGSHI GdTQcGJs